Effective TiO2-Sulfonated Carbon-derived from Eichhornia crassipes in The Removal of Methylene Blue and Congo Red Dyes from Aqueous Solution - Iis Intan Widiyowati; Mukhamad Nurhadi; Muhammad Hatami; Lai Sin Yuan (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
The study of TiO2-sulfonated carbon-derived from Eichhornia crassipes (TiO2/SCEC), as an effective adsorbent to remove Methylene blue (MB) and Congo red (CR) dyes from aqueous solution, has been conducted. The preparation steps of TiO2/SCEC adsorbent involved the carbonisation of E. crassipes powder at 600 °C for 1 h, followed by sulfonation of carbon for 3 h and impregnation through titanium(IV) isopropoxide (500 µmol). The physical properties of the adsorbents were characterized by using X-ray fluorescence (XRF), Fourier transform infrared, X-ray diffraction (XRD), Scanning electron microscopy with Energy dispersive X-ray (SEM-EDX), Thermogravimetric analysis (TGA) and nitrogen adsorption-desorption studies. The dye removal study using TiO2/SCEC adsorbent was carried out by varying of contact time, adsorbent dosage, initial dye concentration, pH, particles size of adsorbent and temperature. The kinetics models were determined by the effects of contact time and the thermodynamic parameters (ΔH, ΔS, and ΔG), which were calculated by the effects of temperature. The results showed that the maximum dye removal capacity of TiO2/SCEC were 18.8 mg.g-1 for MB and 36.5 mg.g-1 for CR. The removal of MB and CR dyes using TiO2/SCEC adsorbent performed a pseudo-second order kinetic models with spontaneity. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).